Proses Branding Melalui Pengelolaan Media Sosial pada PT. SDO - Aat Ruchiat Nugraha; Chasanah Utami Putri (Cakrawala - Jurnal Humaniora, 2020)
With the development of the 4.0 industrial revolution, businesses are encouraged to expand their businesses with digital developments while developing their public relations activities along with the development of communication technology. In the era of the industrial revolution, one of the most effective ways of branding is to use social media, especially Instagram. In this report the author intends to report how PT SDO, which is a company that was born in the era of the industrial revolution 4.0, carried out the branding process through the management of Instagram social media. This report is written using descriptive qualitative method. The data used are the results of observations, interviews and also library data obtained from related books. The results in this report note that the branding process through social media management PT SDO adopted the branding concept from Keller specifically about the factors that constitute brand image, namely the strength of brand associations, the benefits of brand associations, and the uniqueness of brand association.